Predictive value of General Movement Assessment for preterm infants' development at 2 years − implementation in clinical routine in a non-academic setting. (March 2017) - De Bock, Freia; Will, Heike; Behrenbeck, Ulrike; Jarczok, Marc N.; Hadders-Algra, Mijna; Philippi, Heike
Highlights: General Movement Assessment (GMA) can successfully be implemented in a non-academic setting. Practical tips for implementing GMA in clinical routine. GMA predicts neurodevelopment of preterm infants in a non-academic setting. Abstract: Background: General movements (GM) are used in academic settings to predict developmental outcome in infants born preterm. However, little is known about the implementation and predictive value of GM in non-academic settings. Aims: The aim of this study is twofold: To document the implementation of GM assessment (GMA) in a non-academic setting and to assess its predictive value in infants born preterm. Methods and procedures: We documented the process of implementing GMA in a non-academic outpatient clinic. In addition, we assessed the predictive value of GMA at 1 and 3 months' corrected age for motor and cognitive development at 2 years in 122 children born <33 weeks' gestation. Outcome at two years was based upon the Bayley Scales of Infant Development-II (mental/psychomotor developmental index (MDI, PDI)) and a neurological examination. The infants' odds of atypical outcome (MDI or PDI ≤70 or diagnosis CP) and the predictive accuracy of abnormal GMA were calculated in a clinical routine scenario, which used all available GM information (primarily at 3 months or at 1 month, when 3 months were not available). In addition, separate analysis was undertaken for the samples of GMA at 1 and 3 months. Outcomes and results: Tips to facilitate GMA implementation are described. In our clinical routine scenario, children with definitely abnormal GM were more likely to have an atypical two-year outcome than children with normal GM (OR 13.2 (95% CI 1.56; 112.5); sensitivity 55.6%, specificity 82.1%). Definitely abnormal GM were associated with reduced MDI (−12.0, 95% CI −23.2; −0.87) and identified all children with cerebral palsy (CP) in the sample of GMA at 3 months only. Conclusions and implications: GMA can be successfully implemented in a non-academic outpatient setting. In our clinical routine scenario, GMA allowed for adequate prediction of neurodevelopment in infants born preterm, thereby allaying concerns about diagnostic accuracy in non-academic settings.